Cognitive Brain Lateralization Through Neurovascular Coupling in Healthy Subjects: A Statistical Complexity Analysis - Chacon-Pacheco, M; Rojas-Pescio, H (American Physiological Society, 2025)
Human sensory, cognitive, and motor processes often result in asymmetric cerebral hemisphere activation, observable through neurovascular coupling (NVC). Brain lateralization enables simultaneous performance of distinct functions, enhancing cognitive capacity. This study examined cognitive lateralization through NVC responses to the Addenbrooke s Cognitive Examination-III (ACE-III) assessment, using entropy-based methods and statistical complexity measures (SCM). We tested whether applying dispersion entropy (DE) to cerebral blood velocity (CBv), critical closing pressure (CrCP), and resistance area-product (RAP) signals could identify significant hemispheric differences during cognitive tasks. Statistical analysis revealed SCM effectively detected lateralization (best p-value = 0.001), whereas entropy alone did not differentiate hemisphere activity. Furthermore, cognitive stimulation (attention, fluency, language, memory, and visuospatial tasks) generally produced lower SCM values compared to baseline, predominantly in the dominant hemisphere. These findings indicate that NVC exhibits distinct complexity patterns based on hemisphere dominance and cognitive domain stimulated. Additionally, comparison with prior ACE-III analyses, using population-normalized mean peak change, reinforces that advanced biomedical-oriented information theory methods, such as DE and SCM, offer valuable insights into cerebral lateralization mechanisms and NVC responses during cognitive stimulation. © 2025 The Author(s). Physiological Reports published by Wiley Periodicals LLC on behalf of The Physiological Society and the American Physiological Society.